2002
DOI: 10.1046/j.1365-2559.2002.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine differentiation and prognosis in breast adenocarcinoma

Abstract: In this study we confirm that neuroendocrine differentiation can be identified in a subset (10-18%) of human breast carcinomas. This phenomenon appears to have no relationship to established prognostic factors or patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 33 publications
6
112
2
5
Order By: Relevance
“…The importance of this definition is highlighted by 2 studies that showed that focal NE differentiation had no prognostic significance as compared with breast carcinoma NOS. 8,21 Because NEC is an uncommon and newly defined entity, to date there have been only 5 series reported 9,11-14 using this diagnostic criteria. None of those series was case controlled, all had relatively small numbers of patients, and they reached conflicting conclusions about the significance of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this definition is highlighted by 2 studies that showed that focal NE differentiation had no prognostic significance as compared with breast carcinoma NOS. 8,21 Because NEC is an uncommon and newly defined entity, to date there have been only 5 series reported 9,11-14 using this diagnostic criteria. None of those series was case controlled, all had relatively small numbers of patients, and they reached conflicting conclusions about the significance of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors, all with neoplastic cellularity greater than 50%, were obtained with appropriate ethical approval and are detailed in Supplementary Tables 2 and 3. The breast tumors were primary operable invasive breast cancers from the Nottingham City Hospital Tumor Bank (Elston and Ellis, 1991;Parker et al, 2001;Miremadi et al, 2002). Ovarian tumors were from Addenbrooke's Hospital, Cambridge.…”
Section: Primary Tumors and Cell Linesmentioning
confidence: 99%
“…Em recente estudo, Weigelt et al demonstraram que o carcinoma celular mucinoso, variante do TNPM, possui características moleculares distintas do carcinoma ductal (23) . O carcinoma de pequenas células, outra variante do TNPM, demonstra prognóstico muito pior que outras histologias (12,15,16,24) . O NE-DCIS foi descrito pela primeira vez em 1985 (3) .…”
Section: Discussionunclassified
“…Os subtipos histológicos identificados foram sólido, de pequenas células, de grandes células, celular mucinoso, carcinoide atípico e carcinoma ductal neuroendócrino in situ (NE-DCIS) (20) . Alguns carcinomas de mama expressam áreas de diferenciação neuroendócrina, < 50% das células, porém sem impacto no prognóstico (12,21) .…”
Section: Introductionunclassified